2016
DOI: 10.5152/tao.2016.1713
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Sphenopalatine Artery Ligation in Posterior Epistaxis: Retrospective Analysis of 30 Patients

Abstract: Objective: Although posterior epistaxis is rarely seen, it is an important medical problem that both decreases the quality of life of the patient and causes difficulties in the management for otorhinolaryngologists. In this study, we aimed to present the results of 30 patients who underwent transnasal endoscopic sphenopalatine artery ligation (TESPAL) for posterior epistaxis in our department. Methods:The records of 30 patients who underwent TESPAL from January 2014 to April 2016 were analyzed retrospectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Male predominance was seen in patients undergoing ESPAL in our study which was similar to study done by Ismi O, et al 10 Ibrahim, et al 8 Bijaya K et al 6 Pramanik and Adhikari 11 revealed O positive group as the most predominant (35.5%) and AB group as the least prevailing group among Nepalese population which was similar to our study where O positive blood group was found to be predominant 65.85%.…”
Section: Discussionsupporting
confidence: 90%
“…Male predominance was seen in patients undergoing ESPAL in our study which was similar to study done by Ismi O, et al 10 Ibrahim, et al 8 Bijaya K et al 6 Pramanik and Adhikari 11 revealed O positive group as the most predominant (35.5%) and AB group as the least prevailing group among Nepalese population which was similar to our study where O positive blood group was found to be predominant 65.85%.…”
Section: Discussionsupporting
confidence: 90%
“…In Yüksel's [13] study, 80.3% of the patients had comorbidities, with the most common comorbidity being HT. In 30 disease studies conducted by Ismi, [6] the prevalence of HT was 56.6%. The prevalence of HT in patients with epistaxis varies between 24 and 64%.…”
Section: Discussionmentioning
confidence: 96%
“…Although posterior nasal tampons may be used in patients with posterior epistaxis, in recent years, both the morbidity rates and hospitalization duration of these patients have decreased due to the use of transnasal endoscopic sphenopalatine artery ligation (TESPAL) and arterial embolization. [6] While individuals aged over 70 are at a higher risk of epistaxis, they are three times more likely to receive medical care for epistaxis than pediatric patients. [7] Our aim is to define additional features of epistaxis patients in the geriatric population and to have an administrative idea.…”
mentioning
confidence: 99%
“…The overall success rate of SPA cauterization was 87.1% which comes in agreement with this study. İsmi et al [15] conduct retrospective analysis of 30 patients with endoscopic sphenopalatine artery ligation in posterior epistaxis. The overall success rate of SPA ligation was 90% which comes in agreement with this study Saraceni et al [9] perform 11 years of follow-up of 98 patients submitted to SPA surgery for epistaxis.…”
Section: Discussionmentioning
confidence: 99%